Forest Health Assessment in Agroforestry System in Sisimeni Sanam Permanent Production Forest Area as the Upstream of Manikin Baki Watershed: Case Study of Niukbaun Village, West Amarasi District, Kupang Regency, East Nusa Tenggara - Butung, Yunita; Seran, Wilhelmina; Mau, Astin Elise; Kaho, Norman P.L.B. Riwu (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Watersheds (DAS) function as a reservoir, storage, and distribution of water, and divided into upstream, middle, and downstream areas. The Manikin Baki watershed in East Nusa Tenggara faces problems of erosion, land degradation, and illegal grazing. An afforestation program by Nusa Cendana University, the Ford Foundation and the NTT Forestry Office since 1982 has successfully created an agroforestry area in the Sisimeni Sanam Permanent Forest Area, but there are still environmental problems that need to be addressed. This study assessed the health of agroforestry forests in the Manikin Baki watershed using the Forest Health Monitoring (FHM) method with vitality indicators with tree damage parameters, productivity with base area parameters (LBDS) and tree volume, biodiversity with diversity and species richness parameters, and site quality with cation exchange capacity (CEC) and soil pH parameters. The results showed that the vitality indicator was in the healthy category. Productivity indicators show that the results of LBDS and volume calculations can be used to compare changes in the next period. Biodiversity indicators show that the index of richness and diversity of stand species is less stable, causing a decrease in biodiversity. Site quality indicators show high CEC values and neutral pH. This agroforestry system has great potential to strengthen the sustainability of the biotic and abiotic environment in the upstream area of the Manikin Baki watershed through the positive contribution of the four forest health indicators.